Juridical Review of Duties and Functions of Bhabinkamtibmas In Maintaining Security and Order in Sempu Village, Blora Regency - Suwoko Suwoko; Edi Pranoto (Jurnal Indonesia Sosial Sains, 2023)
Indonesia is a constitutional state with laws governing all aspects of social life, including the Indonesian National Police (Polri), which is responsible for maintaining public order and security, law enforcement, protection, and service to the community. To enhance community policing, Polri adopted the concept of "Polmas" in 2005. A study was conducted in Sempu Village, Kunduran District, Blora Regency, to examine the obstacles and efforts in maintaining security and order by the Bhabinkamtibmas unit. Bhabinkamtibmas carries out duties and functions, such as Sambang and appeal activities, and visits to the community. The study found that the Bhabinkamtibmas unit faces obstacles such as low human resources and dual duties. To overcome these obstacles, structured approaches to the community were taken, including inviting the community to chat and attend counseling activities, leading to better communication and gathering of information from the community